An examination of co-operative strategies towards policing stocktheft in the Kwazulu-Natal province - Manganyi, Foster Mzamani (Acta criminologica, 2018)
Stocktheft, as a rural crime, has over the years either been under researched or not been researched in any depth by academics, researchers and scholars in the field of Criminology and Criminal Justice. This lack of criminological attention is despite the fact that, within the livestock farming sector, stocktheft has the biggest economic impact of all rural crime. Relevant stakeholders across the KwaZulu-Natal (KZN) province in South Africa have attempted to initiate various co-operative strategies in a bid to address livestock theft, which remains at one of the highest levels in South Africa. Instituting co-operative strategies in this province has proved to a difficult obstacle to overcome. This article presents selected findings from studies and publications on policing of stocktheft. The findings of this study enabled the researchers to recommend that effective collaboration structures between all relevant stakeholders in the policing of stocktheft in KwaZulu-Natal Province should be incorporated into anti-stocktheft operations by means of the development of a set of good practices guidelines - all to assist in solving the problems relating to this form of rural crime. Reference in the article is also made to the use of Deoxyribonucleic Acid (DNA) technology as an aid to traditional methods of combating the direct impact of stocktheft on livestock farmers in the formal and informal rural economies. The utilising of DNA technology assists anti-livestock theft efforts by providing considerable evidence resulting from physical matching, soil analyses and manure samples. DNA technology, therefore, enables commercial and emerging subsistence livestock farmers, as well as other interested stakeholders, to more effectively combat this crime by obtaining successful prosecutions in court.